New Insights on the Mechanism of Fatty Acids as Buccal Permeation Enhancers - Cristina Padula; Silvia Pescina; Sara Nicoli; Patrizia Santi (MDPI AG, 2018)
Buccal mucosa has recently received much attention as a potential route for systemic delivery of drugs, including biologics and vaccines. The aim of this work was to gain insight into the mechanism of fatty acids as buccal permeation enhancers, by studying the effect of a series of medium and long chain fatty acids on the permeation of a model high molecular weight and hydrophilic molecule, fluorescein isothiocyanate labelled dextran (FD-4, m.w. 4 kDa) across porcine esophageal epithelium. A parabolic relationship between fatty acid lipophilicity and enhancement was obtained, regardless of the presence and number of double bonds. The relationship, which resembles the well-known relationship between permeability and lipophilicity of transdermal delivery, presents a maximum value in correspondence of C10 (logP approx. 4). This is probably the ideal lipophilicity for the fatty acid to interact with the lipid domains of the mucosa. When the same analysis was performed on skin data, the same trend was observed, although the maximum value was reached for C12 (logP approx. 5), in agreement with the higher lipophilicity of the skin. The results obtained in the present work represent a significant advancement in the understanding of the mechanisms of action of fatty acids as buccal penetration enhancers.